Development of small-molecule reporters for fluorescence imaging of enzymes function and application - Cheong, Haolun (Nanyang Technological University, 2020)
Much attention has been placed in understanding the various enzymes activities due to their vital roles in mammalian and bacterial cells, which is closely associated with the progression of many pathological conditions such as tumor proliferation, bacterial infection and neurological disorder. Therefore, developing a selective and sensitive platform to detect and monitor enzyme activities is essential in elucidating the biological functions and crucial for early diagnostic and treatments of diseases. Among the various techniques developed to monitor enzyme function, optical imaging, which utilize light to obtain the image of the cellular function in the living cells has been widely exploited to detect and visualize enzyme activity in living cells. It widespread used is mainly due to its ease of operation, high sensitivity, low cost and high-throughput capabilities. Hence, in this thesis, I had utilized the advantages of optical imaging to design various new novel and sensitive fluorescent reporter capable of visualizing selected enzyme, furin and β-lactamase that have similar catalytic activities, at the target cellular compartment. Furin is located at different organelle and each location contributed to different biological roles in the pathological condition. Therefore, the specific detection of enzyme activity at targeted compartment helps to elucidate furin biological function. Thus in chapter 2, a light-activatable fluorescent reporter was constructed to control the visualization of furin activities on the cellular surface. The peptide-based fluorescent reporter was conjugated with a fatty acid moiety and a photo-removable moiety so that it can efficiently immobilize on the lipid compartment of the cellular membrane. Moreover, the photo-removable moiety enables spatiotemporal control of the fluorescent reporter through external light illumination to control the time and location to conduct imaging of endogenous proteolytic enzymes in the living cells. Furthermore, as furin involvement in the pathological pathway differs at different compartment, specific detection of furin at Golgi apparatus is also important for in-depth analysis of furin biological roles. Hence in chapter 3, I had designed a peptide-based fluorescent reporter to localized on the Golgi apparatus to conduct real-time visualization of furin activities located at Golgi. The probe was a conjugation of Golgi targeting sphingosine moiety and a furin-responsive peptide probe to efficiently localize on the Golgi apparatus in order to specifically conduct imaging of proteolytic enzyme in the living cells. Moreover, furin is closely associated with the progression of various cancers including non-small cell lung carcinomas, head and neck squamous cell carcinomas, and breast cancer. Therefore, in chapter 4, we developed a reporter capable to specifically target tumor cells for visualization and other potential biomedical applications such as disease treatment. We utilized a peptide-caged metabolic precursor that can be activated by furin-like proteolytic activities on selected cells. Upon triggered by furin, the unnatural glycan will be released and will undergo intrinsic metabolism by the cells to exogenously expressed the azide (N3-) groups on the cell surfaces, which can be used for visualization or subsequent therapeutic option. Similarly, in bacterial cells, enzymes also play vital roles in various biological functions. Of interests, β-lactamases activity is a serious medical concern as it promotes the bacteria resistance against the conventional antibiotic drugs. Therefore, in order to better understand the enzyme functions and combat against drug resistance, we demonstrated the use of metabolic-mediated fluorescent reporter to specifically detect and visualize class C β-lactamases enzyme in resistant bacteria for in vivo application in chapter 5. A bulky DBCO group was conjugated to the 7’ position of the cephalosporin β-lactam ring on the fluorescent reporter, which can be used for subsequent labeling on the bacterial cell surface and will also acts as a steric hindrance to improve the selectivity toward class C β-lactamases.